Answer:
it si this
Explanation:
Simplifying
4y + -10 = 5 + -1y
Reorder the terms:
-10 + 4y = 5 + -1y
Solving
-10 + 4y = 5 + -1y
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Add 'y' to each side of the equation.
-10 + 4y + y = 5 + -1y + y
Combine like terms: 4y + y = 5y
-10 + 5y = 5 + -1y + y
Combine like terms: -1y + y = 0
-10 + 5y = 5 + 0
-10 + 5y = 5
Add '10' to each side of the equation.
-10 + 10 + 5y = 5 + 10
Combine like terms: -10 + 10 = 0
0 + 5y = 5 + 10
5y = 5 + 10
Combine like terms: 5 + 10 = 15
5y = 15
Divide each side by '5'.
y = 3
Simplifying
y = 3